Concentrations of tylvalosin and 3‐O‐acetyltylosin attained in the synovial fluid of swine after administration by oral gavage at 50 and 5 mg/kg. Issue 6 (17th April 2016) - Canning, P.; Bates, J.; Hammen, K.; Coetzee, J.; Wulf, L.; Rajewski, S.; Wang, C.; Karriker, L.
Abstract : The objectives of this study were to determine the concentration of tylvalosin (TVN) and its metabolite, 3‐O‐acetyltylosin (3AT) in the synovial fluid of growing pigs when administered as a single bolus by oral gavage at target doses of 50 mg/kg (Trial 1) and 5 mg/kg (Trial 2). TVN is a water soluble macrolide antimicrobial used in swine production. The stability of the drug in synovial fluid samples stored at −70 °C up to 28 days was also evaluated in Trial 2. In Trial 1, eight pigs were randomly assigned to one of eight time points for euthanasia and synovial fluid collection: 0, 1, 2, 3, 4, 6, 9, 12 h postgavage. For Trial 2, 24 pigs were randomly allocated to one terminal collection time point at 0, 2, 4, 6, 8 or 10 h postgavage. Synovial fluid was analyzed to determine TVN and 3AT concentrations. TVN and 3AT were detected in Trial 1 at all time points, except 0 h. At 2 h postgavage for trial 2, the mean concentrations peaked at 31.17 ng/mL (95% CI: 18.62–52.16) for TVN and at 58.82 ng/mL (95% CI: 35.14–98.46) for 3AT. Storage duration did not impact TVN or 3AT concentrations ( P ‐value 0.9732).